A rare and challenging case of pulmonary mycobacterium genavense in an immunocompetent adult / Nur ‘Aini Eddy Warman and Nurul Yaqeen Mohd Esa. - Eddy Warman, Nur ‘Aini; Mohd Esa, Nurul Yaqeen (Universiti Teknologi MARA Cawangan Selangor, 2018)
Mycobacterium genavense, a non-tuberculous mycobacterium (NTM), usually affects patients severely immunodeficient from human immunodeficiency virus (HIV) infection or any other immunocompromised states. We reported a case in a 70-year-old female with well-controlled diabetes and history of proximal cystic bronchiectasis. She presented with 2 months history of cough, haemoptysis, and night sweats of which serial sputa were positive for acid-fast bacilli and the culture repeatedly grew M. genavense. Treatment with rifampicin, ofloxacin, and clarithromycin was complicated with drug-induced liver injury and intractable gastrointestinal side effects. We also presented a brief review of relevant literature.